Long-term use of ticagrelor in patients with prior myocardial infarction - Bonaca, Marc P; Bhatt, Deepak L; Cohen, Marc; Steg, Philippe Gabriel; Storey, Robert F; Jensen, Eva C; Magnani, Giulia; Bansilal, Sameer; Fish, M Polly; Im, Kyungah; Bengtsson, Olof; Oude Ophuis, Ton; et al. (The New England journal of medicine, 2015)
BACKGROUND: The potential benefit of dual antiplatelet therapy beyond 1 year after a myocardial infarction has not been established. We investigated the efficacy and safety of ticagrelor, a P2Y12 receptor antagonist with established efficacy after an acute coronary syndrome, in this context. METHODS: We randomly assigned, in a double-blind 1:1:1 fashion, 21,162 patients who had had a myocardial infarction 1 to 3 years earlier to ticagrelor at a dose of 90 mg twice daily, ticagrelor at a dose of 60 mg twice daily, or placebo. All the patients were to receive low-dose aspirin and were followed for a median of 33 months. The primary efficacy end point was the composite of cardiovascular death, myocardial infarction, or stroke. The primary safety end point was Thrombolysis in Myocardial Infarction (TIMI) major bleeding. RESULTS: The two ticagrelor doses each reduced, as compared with placebo, the rate of the primary efficacy end point, with Kaplan-Meier rates at 3 years of 7.85% in the group that received 90 mg of ticagrelor twice daily, 7.77% in the group that received 60 mg of ticagrelor twice daily, and 9.04% in the placebo group (hazard ratio for 90 mg of ticagrelor vs. placebo, 0.85; 95% confidence interval [CI], 0.75 to 0.96; P=0.008; hazard ratio for 60 mg of ticagrelor vs. placebo, 0.84; 95% CI, 0.74 to 0.95; P=0.004). Rates of TIMI major bleeding were higher with ticagrelor (2.60% with 90 mg and 2.30% with 60 mg) than with placebo (1.06%) (P<0.001 for each dose vs. placebo); the rates of intracranial hemorrhage or fatal bleeding in the three groups were 0.63%, 0.71%, and 0.60%, respectively. CONCLUSIONS: In patients with a myocardial infarction more than 1 year previously, treatment with ticagrelor significantly reduced the risk of cardiovascular death, myocardial infarction, or stroke and increased the risk of major bleeding. (Funded by AstraZeneca; PEGASUS-TIMI 54 ClinicalTrials.gov number, NCT01225562.).
Keywords: Double-Blind Method; Hemorrhage; kombinovaná farmakoterapie; Kaplan-Meier Estimate; krvácení; inhibitory agregace trombocytů; Humans; Drug Therapy, Combination; kardiovaskulární nemoci; lidé středního věku; Middle Aged; antagonisté purinergních receptorů P2Y; adenosin; Risk; Kaplanův-Meierův odhad; riziko; Cardiovascular Diseases; Intracranial Hemorrhages; Aspirin; mužské pohlaví; Drug Administration Schedule; Myocardial Infarction; sekundární prevence; Secondary Prevention; ženské pohlaví; rozvrh dávkování léků; Platelet Aggregation Inhibitors; infarkt myokardu; lidé; ticagrelor; intrakraniální krvácení; Purinergic P2Y Receptor Antagonists; Adenosine; Aged; senioři; Male; Ticagrelor; dvojitá slepá metoda; Female